2011
DOI: 10.5380/rf.v41i1.21179
|View full text |Cite
|
Sign up to set email alerts
|

CARACTERÍSTICAS DAS DIMENSÕES DAS FIBRAS E ANÁLISE DO ÂNGULO MICROFIBRILAR DE Toona ciliata CULTIVADA EM DIFERENTES LOCALIDADES

Abstract: ResumoO presente trabalho teve como objetivos determinar as dimensões das fibras e avaliar o ângulo microfibrilar da madeira de cedro australiano aos 4 anos de idade, no sentido axial base-topo, proveniente dos municípios de Cana Verde, Campo Belo e Santo Antônio do Amparo, localizados na região do sul de Minas Gerais. A partir da altura comercial de cada árvore, foi retirada uma tábua com 5 m de comprimento, da qual foram retiradas amostras em três posições: base, 50 e 100%. Os elementos anatômicos foram mens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
2
0
3
Order By: Relevance
“…Em Adrianópolis, PR, plantios de 11 anos chegaram a atingir 43 cm de DAP (Ricken et al, 2011). Em plantios mais jovens com apenas quatro anos de idade, em Minas Gerais Ziech (2008) obteve DAP médio de 17,5 cm e altura média de 11,4 m. Embora se trate de uma espécie com grande potencial para a silvicultura comercial brasileira, ainda pouco se sabe sobre os aspectos tecnológicos de sua madeira, principalmente com referência à espécie introduzida nos reflorestamentos no Brasil (Ribeiro et al, 2011).…”
unclassified
“…Em Adrianópolis, PR, plantios de 11 anos chegaram a atingir 43 cm de DAP (Ricken et al, 2011). Em plantios mais jovens com apenas quatro anos de idade, em Minas Gerais Ziech (2008) obteve DAP médio de 17,5 cm e altura média de 11,4 m. Embora se trate de uma espécie com grande potencial para a silvicultura comercial brasileira, ainda pouco se sabe sobre os aspectos tecnológicos de sua madeira, principalmente com referência à espécie introduzida nos reflorestamentos no Brasil (Ribeiro et al, 2011).…”
unclassified
“…However, in populations of Toona ciliata from three different locations, it was found, in relation to the results of the analyzes carried out in the base-top positions of the trees, for the microfibril angle that these differ from those found in the literature, as MFA from the three locations increased in the axial direction, in the bottom-top direction, and this can be explained by the silvicultural and environmental influences that may have occurred (Ribeiro et al, 2011).…”
Section: Resultsmentioning
confidence: 53%
“…Tropical species such as Anadenanthera peregrina, Ochroma pyramidale, and Schizolobium parahyba Var amazonicum showed the same type of increasing radial variation from pith to bark as J. copaia (Rueda and Williamson, 1992;Valente et al, 2013;Lobão et al, 2012) and the same behavior was found in tropical forest plantation species such as Guazuma crinita, Schizolobium parahyba, Tectona grandis, Toona ciliata, (Chavesta et al, 2020;Lima et al, 2021;Melo et al, 2018;Ribeiro et al, 2011). On the other hand, the tropical species Cariniana legalis also did not present any significant trend of radial variation in the pith-bark direction, the same as the species H. crepitans (Lima et al, 2011;Ribeiro et al, 2011), which does not exist a significant difference in the radial variation of wood in the species H. crepitans is favorable for industrial transformation processes (Plaster et al, 2008;Rios et al, 2018).…”
Section: Discussionmentioning
confidence: 71%